Gut Mycobiome: Latest Findings and Current Knowledge Regarding Its Significance in Human Health and Disease - Bogdan Severus Gaspar; Oana Alexandra Roşu; Robert-Mihai Enache; Monica Manciulea (Profir); Luciana Alexandra Pavelescu; Sanda Maria Creţoiu (Journal of Fungi)
The gut mycobiome, the fungal component of the gut microbiota, plays a crucial role in health and disease. Although fungi represent a small fraction of the gut ecosystem, they influence immune responses, gut homeostasis, and disease progression. The mycobiome’s composition varies with age, diet, and host factors, and its imbalance has been linked to conditions such as inflammatory bowel disease (IBD) and metabolic disorders. Advances in sequencing have expanded our understanding of gut fungi, but challenges remain due to methodological limitations and high variability between individuals. Emerging therapeutic strategies, including antifungals, probiotics, fecal microbiota transplantation, and dietary interventions, show promise but require further study. This review highlights recent discoveries on the gut mycobiome, its interactions with bacteria, its role in disease, and potential clinical applications. A deeper understanding of fungal contributions to gut health will help develop targeted microbiome-based therapies.